초등학생 어머니의 양육스트레스, 대처방식 및 한방진단시스템과의 연관성 연구 - 임정화; Jung Hwa Lim; 이인선; In Sun Lee; 정인철; In Chul Jung; 황보민; Bo Min Hwang; 정민정; Min Jeong Jeong (동의신경정신과학회지, 2010)
Objectives: This study was to investigate the associations of Parent Stress Index(PSI), Way of Coping Checklist(WCC), and Diagnostic System of Oriental Medicine(DSOM) in mothers of elementary school children. Methods: In the study, K-PSI-SF, WCC, and DSOM were carried out on 202 mothers of ○○elementary school children during June, 2010. Cross tabulation analysis was used to verify the association of PSI, WCC and DSOM. Results: 1. The most common pathogenic factor was Dampness(濕) in total subjects. 2. The score of problem-focused coping methods showed significant difference in PSI grades. 3. The zp and sc10 of Qi deficiency(氣虛), Blood deficiency(血虛), Qi-Stagnation(氣滯), Insufficiency of Yang(陽虛), Heat(熱), Dampness(濕), Dryness(燥), Liver(肝), Heart(心), and Kidney(腎) showed significant difference in PSI grades. 4. The score of total PSI and PSI subscale had negative correlations with problem-focused coping methods. 5. The score of total PSI had positive correlations with Qi-Stagnation(氣滯), Dampness(濕), Dryness(燥), Heart(心), and Kidney(腎) in total subjects. Conclusions: This study provides insights on associations of parenting stress coping methods and diagnostic system in Oriental Medicine. Furthermore, the study shows positive correlations among Qi-Stagnation(氣滯), Dampness(濕), Dryness(燥), Heart(心), Kidney(腎) and PSI, and negative correlations between PSI and Problem-focused coping methods, all with statistical significance.